Perlindungan Hukum Terhadap Apoteker Dalam Pelaksanaan Akta Perjanjian Kerjasama Pengelolaan Apotek - Wuri Wardani (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Pattern cooperation pharmacy management has not been regulated with certainty, its implementation is only based on an agreement between the investor and the pharmacist. This Study carried out to analyze legal protection for pharmacists in the procurement and storage of specific types of medicines psychotropics and narcoticsbased on the deed of agreement cooperation pharmacy management. The problem formulation in this research is how to procure and store specific types of medicinespsychotropics and narcotics? and what is the legal protection for pharmacists in managing pharmacies related to the procurement and storage of specific types of medicinespsychotropics and narcotics? The research method uses normative legal research which is supported by empirical data from interviews with sources analyzed using qualitative analysis methods.The research results show the conclusion that: First, procurement of specific types of drugs psychotropics and narcoticsunder the authority of APA which is carried out through an order letter made and signed by APA and affixed with the pharmacy stamp. Storage of type-specific medications psychotropics and narcotics stored in a special room and place. Second, legal protection for pharmacists in the agreement deed cooperation management of pharmacy procurement of special types of medicines psychotropics and narcotics still minimal because of the clause that does not favor pharmacists and the absence of special clauses regarding rights, obligations and authorities between APA and PSA regarding specific types of drugs psychotropics and narcotics, protection efforts can be carried out preventively and repressively.